The conserved disulfide bond of human tear lipocalin modulates conformation and lipid binding in a ligand selective manner - Gasymov, Oktay K. (2011)
The primary aim of this study is the elucidation of the mechanism of disulfide induced alteration of ligand binding in human tear lipocalin (TL). Disulfide bonds may act as dynamic scaffolds to regulate conformational changes that alter protein function including receptor-ligand interactions. A single disulfide bond, (Cys61-Cys153), exists in TL that is highly conserved in the lipocalin superfamily. Circular dichroism and fluorescence spectroscopies were applied to investigate the mechanism by which disulfide bond removal effects protein stability, dynamics and ligand binding properties. Although the secondary structure is not altered by disulfide elimination, TL shows decreased stability against urea denaturation. Free energy change (ΔG(0)) decreases from 4.9± 0.2 to 2.1± 0.3 kcal/mol with removal of the disulfide bond. Furthermore, ligand binding properties of TL without the disulfide vary according to the type of ligand. The binding of a bulky ligand, NBD-cholesterol, has a decreased time constant (from 11.8± 0.2 to 3.3 s). In contrast, the NBD-labeled phospholipid shows a moderate decrease in the time constant for binding, from 33.2± 0.2 to 22.2± 0.4 s. FRET experiments indicate that the hairpin CD is directly involved in modulation of both ligand binding and flexibility of TL. In TL complexed with palmitc acid (PA-TL), the distance between the residues 62 of strand D and 81 of loop EF is decreased by disulfide bond reduction. Consequently, removal of the disulfide bond boosts flexibility of the protein to reach a CD-EF loop distance (24.3 Å, between residues 62 and 81), which is not accessible for the protein with an intact disulfide bond (26.2 Å). The results suggest that enhanced flexibility of the protein promotes a faster accommodation of the ligand inside the cavity and energetically favorable ligand-protein complex.